Air Mobility : A Brief History of the American Experience - Owen, Robert C., 1951- (Book collections on Project MUSE., 2013)
Global air mobility is an American invention. During the twentieth century, other nations developed capabilities to transport supplies and personnel by air to support deployed military forces. But only the United States mustered the resources and will to create a global transport force and aerial refueling aircraft capable of moving air and ground combat forces of all types to anywhere in the world and supporting them in continuous combat operations. Whether contemplating a bomber campaign or halting another surprise attack, American war planners have depended on transport and tanker aircraft.